Pemanfaatan Media Pembelajaran SPSS untuk Meningkatkan Kemampuan Statistik Siswa SMK - Ramadhani, Rahmi; Sribina, Nuraini (Jurnal SOLMA, 2019)
This community service was carried out in the form of a workshop on utilization of SPSS learning media in mathematics learning for vocational high school students in SMK PAB 12 Saentis, Percut Sei Tuan, Deli Serdang, North Sumatera. The target of this service are: 1) to increase students understanding of SPSS learning media in mathematics learning; 2) to improve students' skill in using SPSS learning media; 3) to increase students' knowledge about statistic learning which has an impact of increasing students' statistical skill; and 4) to increase students' motivation and enthusiasm in mathematic learning use SPSS learning media. This method of this community service is carried out in four stages. The first stage is the preparation for software installation. The second stage is the phase of the workshop which filled with tutorials on using SPSS until utilization of SPSS in solving statistic problem. The third stage is workshop method which includes simulation of carried out directly by participants' workshop. The fourth stage is evaluation and giving motivation. The result of this community service activities are as follows: 1) students understand about how to use SPSS in mathematics learning; 2) students are able to use SPSS learning media to solve statistic problem; and 3) students are able to use an active and interactive SPSS learning media until they can improve their statistic skill